Multi layers THz duplexer based on combined graphene patterns. (1st February 2023) - Mohammad Khani, Amir Ali; Fouladian, Majid; Mazloum, Jalil
Abstract: Conducting incident waves to transmission and reflection channels via artificial graphene patterns make it possible to realize a wave duplexer. In this way, a multi layers device is introduced and simulated. The presented device includes two layers, each layer consists of graphene pattern on a dielectric. The exploited patterns are periodic arrays of graphene disks, ribbons and continues graphene sheet. Each consisting part is modeled by passive circuit elements and an equivalent impedance is calculated for proposed device. The device is simulated via full wave numerical approach and equivalent circuit model representation. The target frequency operational range is THz while CST and MATLAB software's are involved in simulations. Highlights: Here we proposed a multi layers THz duplexer based on combined graphene patterns. Conducting THz waves to Output channels via artificial graphene patterns. The presented device includes two layers, each layer consists of graphene pattern on a dielectric. The exploited patterns are periodic arrays of graphene disks, ribbons and continues graphene sheet.